Mulheres, cerâmica e saberes: a artebiografia de Grouze e de Priscila Leonel - Leme, Iriane Du Aguiar [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
With the theme “Grouze and Priscila Leonel: biographies of women in Art”, this research seeks to answer the following question: how to tell new Art Histories from the social markers gender and ethnicity? As a general goal, the research aims to count the artbiographies of the artists Grouze and Priscila Leonel, from their own words and references, and as specific goals, seeks to rename the past, from the selection of female artists and authors that have been made invisible by the unique narrative of history, as well as to present the future, bringing the presence of contemporary artists and authors that has its productions beyond painting. By articulating the words women, ceramics and knowledges, from and through the artbiographies telled, the research seeks to create new routes for looking and making art, far beyond the hegemonic knowledge that permeates our resumes.

Tendo como tema “Grouze e Priscila Leonel: biografias de mulheres em Arte”, a presente pesquisa busca responder a seguinte pergunta: como contar novas Histórias das Artes a partir dos marcadores sociais gênero e etnia? Como objetivo geral, a pesquisa enseja contar as artebiografias das artistas e ceramistas Grouze e Priscila Leonel, a partir de suas próprias palavras e referências, e como específicos, busca a renomeação do passado, a partir da seleção de artistas e autoras mulheres que foram invisibilizadas pela narrativa única da história, bem como presentificar o futuro, trazendo a presença de artistas e autoras contemporâneas que tem suas produções para além da pintura. Ao articular as palavras mulheres, cerâmica e saberes, a partir e através das artebiografias contadas, a pesquisa busca criar novas rotas para o olhar e fazer Arte, para muito além do saber hegemônico que permeia nossos currículos.
Women, ceramics and knowledge: the artebiography of Grouze and of Priscilla Leone
Keywords: Women; Stories; Grouze; Priscila Leonel; Mulheres; Histórias